Resin with thermal crosslinking structure, preparation method of resin, optical adhesive composition, micro lens and preparation method of micro lens
By introducing heat crosslinked structures and nanozirconia particles into the microlens resin, the problems of the existing resins falling refractive index and yellowing of UV light irradiation in high refractive index scenarios are solved, and a microlens material with high refractive index, durability and stability are achieved.
Patent Information
- Application Number
- CN202411992250.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing microlens resin has a decrease in the refractive index in high refractive index usage scenarios and may turn yellow due to UV light irradiation, which cannot meet the needs of high performance and long-term stability.
A resin with a heat crosslinking structure is used, and its structure is prepared by copolymerization reaction of hydroxyl-containing acrylate monomer, epoxy acrylate monomer and carboxy acrylate monomer, combined with the addition of nanozirconia particles to improve refractive index and durability.
It achieves high refractive index, excellent transparency, chemical resistance and long-term reliability, avoids yellowing problems caused by UV light irradiation, and meets the needs of high performance and long-term stability.
Smart Images

Figure BDA0005223896360000021 
Figure BDA0005223896360000022 
Figure BDA0005223896360000031
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and relates to a resin with a thermal cross-linking structure and a preparation method thereof, an optical adhesive composition, a microlens and a preparation method thereof. Background Art
[0002] The optical system materials in existing imaging optical systems such as fax machines, electronic copiers, and solid-state imaging elements use microlenses with lens diameters ranging from 1μm to 100μm. The microlens array (Microlens Array) formed by regularly arranging these microlenses can effectively improve the light extraction efficiency in the display device, increase the screen brightness, and reduce power consumption. In the process of forming such microlenses, a known method is to form a pattern equivalent to a microlens, melt and flow the pattern through heat treatment, and directly use it as a microlens.
[0003] Based on the above formation principle, the existing Chinese patent document 1 (publication number: CN111352301A, publication date: June 30, 2020) discloses a method for forming a thermosensitive resin composition and a microlens. The resin composition is heated at a temperature below 140°C to produce sufficient hot melt flow, so that a microlens with a good shape can be formed. Moreover, the resin composition has the characteristics of high sensitivity and good storage stability. At the same time, the formed microlens has the characteristics of chemical resistance and high transparency. However, the refractive index of the resin composition has decreased, and it cannot meet the requirements of high refractive index use scenarios. In addition, the resin contains aromatic side chains, and there may be a hidden danger of yellowing under UV light irradiation.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a resin with a thermal cross-linking structure and a preparation method thereof, an optical adhesive composition, a microlens and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a resin having a thermally cross-linked structure, and its general structural formula 1 is as follows:
[0008]
[0009] In formula (1), R1 is a methyl group or H, R2 and R4 represent a hydrocarbon group or an alkoxy group, R3 is an epoxy group, R5 and R6 are each independently a hydrogen atom, a halogen atom, a C1-C4 alkyl group or a C1-C4 fluorinated alkyl group, * represents a bond to the main chain, x=0-30mol%, y=40-60mol%, and z=20-40mol%.
[0010] Specifically, when R2 and R4 represent aliphatic hydrocarbon groups, alkyl groups are preferred, and alkyl groups are preferably C1-C20 alkyl groups, and more preferably C1-C6 alkyl groups. The alkyl groups may be linear, branched, or cyclic, and are preferably linear. In addition, the alkyl groups may have substituents or no substituents, for example: methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, hexadecyl, octadecyl, eicosyl, isopropyl, isobutyl, sec-butyl, t-butyl, isopentyl, neopentyl, 1-methylbutyl, isohexyl, 2-ethylhexyl, 2-methylhexyl, cyclohexyl, cyclopentyl, 2-norbornyl, etc.; among them, the alkyl group is preferably methyl or ethyl.
[0011] Specifically, R3 is an epoxy group, including any one of the following formulas (1-1) to (1-6):
[0012]
[0013]
[0014] Wherein, * is a connection site; R7 and R8 are any one of H, C1 to C6 alkyl, C1 to C6 fluoroalkyl, and alkenyl.
[0015] Specifically, the resin having a thermal cross-linking structure has a molecular weight of 7,000 to 10,000, preferably 7,500 to 9,500.
[0016] In a second aspect, the present invention further provides a method for preparing a resin having a thermal cross-linking structure, comprising: mixing a hydroxyl-containing acrylate monomer A, an epoxy acrylate monomer B, and a carboxyl-containing acrylate monomer C for copolymerization; wherein the copolymerization reaction is specifically:
[0017] At a reaction temperature of 60 to 70° C., a hydroxyl-containing acrylate monomer A, an epoxy acrylate monomer B, and a carboxyl-containing acrylate monomer C are mixed in a molar ratio of (0 to 30): (40 to 60): (20 to 40), and are added dropwise to a reaction solvent for polymerization reaction, while a free radical initiator is added for synthesis.
[0018] Specifically, the reaction solvent is halogenated hydrocarbons such as chlorobutane, bromohexane, dichloroethane, 1,6-dibromohexane, and chlorobenzene, ethyl acetate, n-butyl acetate, isobutyl acetate, methyl propionate, and other saturated carboxylic acid esters; ketones such as acetone, methyl ethyl ketone, 4-methyl-2-pentanone, and 2-heptanone; ethers such as tetrahydrofuran, dimethoxyethanes, and diethoxyethanes; and alcohols such as methanol, ethanol, 1-propanol, 2-propanol, and 4-methyl-2-pentanol. The above solvents can be used alone or in combination of two or more.
[0019] Specifically, the free radical initiator includes: one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, azobisisobutylamidine hydrochloride, cyclohexanone peroxide, benzoyl peroxide, and persulfate; preferably azobisisobutyronitrile (AIBN).
[0020] Furthermore, the general structural formula of the hydroxyl-containing acrylate monomer A is as follows:
[0021]
[0022] Based on the structure shown in the above formula (2), the hydroxyl-containing acrylate monomer A may be any one of the structures shown in the following formulas (2-1) to (2-8):
[0023]
[0024] Furthermore, the general structural formula of epoxy acrylic monomer B is as follows:
[0025]
[0026] Based on the structure shown in the above formula (3), the epoxy acrylic monomer B can be any one of the structures shown in the following formulas (3-1) to (3-6):
[0027]
[0028] Furthermore, the general structural formula of the carboxyl-containing acrylate monomer C is as follows:
[0029]
[0030] Based on the structure shown in the above formula (4), the carboxyl group-containing acrylate monomer C may be any one of the structures shown in the following formulas (4-1) to (4-4):
[0031]
[0032] It should be noted that: (1) The reason why the hydroxyl-containing acrylate monomer A and the carboxyl-containing acrylate monomer C are selected as monomers containing non-aromatic groups is that the introduction of aromatic groups will reduce the toughness and impact strength of the resin, and the rigid structure of the aromatic ring will make the molecular chains of the resin more closely arranged, resulting in reduced flexibility and more prone to brittle fracture. In addition, the aromatic ring will also bring the hidden danger of yellowing due to UV aging. Therefore, the inventors of this application abandoned the acrylate monomers containing aromatic groups.
[0033] (2) The hydroxyl group can react with the epoxy group in other monomers to form an ether bond, thereby enhancing the crosslinking degree of the resin. This crosslinked network structure gives the resin excellent thermal stability and mechanical strength, allowing it to maintain a good morphology during high-temperature treatment while improving adhesion. The epoxy acrylic monomer is highly reactive and undergoes a ring-opening reaction with the hydroxyl group to form a stable polymer chain, which not only promotes the crosslinking of the resin, but also improves the heat resistance and chemical resistance of the resin. The carboxyl group of the carboxyl-containing acrylate monomer C can form a stable coordination bond with metal ions such as zirconium ions, stably dispersing the nano-zirconia particles in the resin, which not only helps to improve the transparency of the optical adhesive composition, but also enhances its absorption of light of a specific wavelength, thereby increasing the refractive index of the optical adhesive composition. The introduction of the carboxyl group also helps to increase the polarity of the resin, thereby improving its compatibility with high-refractive-index nano-zirconia particles.
[0034] (3) The introduction of precursor liquid particles significantly increases the refractive index of the optical adhesive composition, thereby increasing the contrast between the exposed area and the unexposed area, which is conducive to the formation of fine patterns. In addition, nanoscale particles can effectively scatter incident light, reduce the penetration depth of light, and thus improve resolution.
[0035] It should be emphasized that the present application optimizes the monomer ratio, that is, mixing the hydroxyl-containing acrylate monomer A, the epoxy acrylate monomer B, and the carboxyl-containing acrylate monomer C in a molar ratio of (0-30): (40-60): (20-40) and adding an appropriate free radical initiator, which can inhibit the free radical polymerization of the resin, reduce the photo-induced aging phenomenon, and improve the adhesion.
[0036] In the third aspect, the present invention provides an optical adhesive composition with thermal reflux effect, which comprises at least the following raw materials in parts by weight: 10 to 20 parts of the above-mentioned resin with thermal cross-linking structure, 3 to 10 parts of precursor liquid particles, 1 to 5 parts of photoinitiator, 0.01 to 0.5 parts of surfactant, and 40 to 80 parts of solvent.
[0037] Specifically, the precursor liquid particles are selected from one or two of ZrO2, TiO2, In2O3, Al2O3, ZnO or SnO2, preferably 3 to 8 parts.
[0038] Furthermore, the average particle size of the precursor liquid particles is 5 to 22 nm, and the refractive index is 1.8 to 2.0. The precursor liquid particles in the present invention are ligand-modified, and have acrylate ligands connected to the surface, and are purchased from JSR, Nippon Shokubai and other companies.
[0039] The inventors of the present application need to emphasize that only when the mass ratio of the precursor liquid particles to the resin with a thermally cross-linked structure is within the range of (2-5):(4-15) can it be ensured that the introduction of the resin with a thermally cross-linked structure does not affect the dispersibility of the precursor liquid particles in the optical adhesive, thereby reducing the agglomeration of nanoparticles and improving the transmittance and refractive index of the composition.
[0040] Specifically, the photoinitiator includes an oxime ester photoinitiator, and the oxime ester photoinitiator includes any one or at least two of OXE-01, OXE-02, OXE-E12 or OXPI-405. OXE-01 is 1-(4-phenylthiophenyl)-octane-1,2-dione-2-benzoic acid oxime ester) (CAS No.: 253585-83-0), and OXE-02 is 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime) (CAS No.: 478556-66-0).
[0041] Specifically, the surfactant includes F-114, F-553, F-562, and F-570 from DIC; FC-135 and FC-170C from 3M; S-211, S-221, S-231, and S-242 from AGC; BYK-300, BYK-301, BYK-302, BYK-306, BYK-310, BYK-313, BYK-320, BYK-366P, BYK-368P, BYK-370, BYK-375, BYK-377, BYK-378, and / or BYK-394 manufactured by BYK. The surfactant can improve the wettability of the developer to the photoresist by reducing the interfacial tension between the developer and the photoresist, thereby promoting the contact and dissolution of the developer and the photoresist. In addition, surfactants can improve leveling, ensure uniform film thickness, and enhance adhesion. These effects together improve the development effect, making the development process smoother and more efficient.
[0042] Specifically, the solvent is alcohols such as 3-methoxy-1-butanol and diacetone alcohol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and N-methyl-2-pyrrolidone; glycol ethers such as diethylene glycol ethyl methyl ether, propylene glycol methyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether; ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate, and propylene glycol methyl ether acetate.
[0043] In addition, the present invention also provides a microlens formed by heat reflowing the optical adhesive composition having a heat reflow effect, which has a good lens shape and a diameter of 1 to 100 μm. In addition, the microlens has excellent chemical resistance and high light transmittance, and can be used for solid-state imaging elements, display element microlens arrays, array flattening film patterns, protective film patterns, insulating film patterns, etc., but is not limited thereto, and is particularly suitable for microlens arrays.
[0044] Specifically, the optical adhesive composition is subjected to spin coating, pre-baking, exposure, development, and then heating and reflowing to form a microlens with a good shape. The specific preparation process is as follows:
[0045] Step 1, first, the optical adhesive composition is coated on a substrate (semiconductor substrate, silicon nitride substrate, quartz substrate, glass substrate, glass substrate with ITO film), and the optical adhesive composition is coated by a spin coater, a coater, a roller coating method, a slit coating method or other coating methods, and then VCD (vacuum desolventizing) is performed for 120 seconds, and then pre-baking is performed to form a coating film, the film thickness is usually 2 to 10 μm; preferably 2 to 4 μm, the pre-baking temperature is 70 to 100 ° C, and the baking time is 0.3 to 10 minutes;
[0046] Step 2, then, the coating film is exposed to light to obtain a film having a target pattern, and ultraviolet rays are irradiated through a mask plate, so that the film cured by ultraviolet rays is brought into contact with a developer to dissolve the unexposed area. After development, the pattern is washed with water and dried with nitrogen. The developer can be an aqueous solution of an alkali metal hydroxide such as potassium hydroxide and sodium hydroxide, an aqueous solution of a quaternary ammonium hydroxide such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline, and can be an alkaline aqueous solution such as an aqueous solution of an amine such as ethanolamine, propylamine, and ethylenediamine;
[0047] Step 3: Finally, heat at 90-150°C for 3-20 minutes to melt the film and use its own surface tension to form microlenses by thermal reflow. The lowest temperature that can form a lens-shaped pattern is defined as the thermal reflow temperature.
[0048] Finally, the present invention also provides an image display device of the above-mentioned microlens array, which includes a liquid crystal display device, an organic light emitting diode, a flexible display, etc., but is not limited thereto, and may also include all known image display devices that can be applied in this technical field.
[0049] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0050] 1) The present invention prepares a resin structure with a heat reflux effect by rationally designing the structure and molar ratio of a hydroxyl-containing acrylate monomer, an epoxy acrylate monomer, and a carboxyl-containing acrylate monomer. The preparation method is simple, low-cost, stable, highly operable, and repeatable. A microlens with a hemispherical shape can be formed, and the formed microlens has excellent transparency, chemical resistance, and long-term reliability. The resin structure can effectively prevent the yellowing of the photoresist due to ultraviolet irradiation, ensure the stability of the performance after long-term use, and combine with high-refractive-index nano zirconium oxide particles to further improve the performance of the material, forming a new type of negative optical adhesive, which not only has excellent optical properties, but also performs well in thermal stability, chemical resistance, and aging resistance, and has broad application prospects.
[0051] 2) The heat-crosslinked resin structure provided by the present invention gives the photoresist good reflow characteristics, can maintain a stable morphology at high temperatures, and can prepare an optical adhesive composition with excellent optical properties and durability; combined with the addition of nano zirconium oxide particles, the refractive index of the optical adhesive composition can be increased to 1.6, meeting the requirements of high-refractive-index optical components. At the same time, the uniform dispersion of nanoparticles is conducive to improving the transmittance of the optical adhesive composition in the visible light band, and can also improve the anti-aging and anti-yellowing properties of the optical adhesive composition. DETAILED DESCRIPTION
[0052] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.
[0053] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments.
[0054] Preparation Example
[0055] This preparation example provides a method for preparing a resin with a thermally cross-linked structure. A hydroxyl-containing acrylate monomer A, an epoxy acrylate monomer B, and a carboxyl-containing acrylate monomer C are mixed in a molar ratio of 10:40:20, and then added dropwise to a butyl acetate solvent for copolymerization. The hydroxyl-containing acrylate monomer A has a structure as shown in formula (2-2), the epoxy acrylate monomer B has a structure as shown in formula (3-1), and the carboxyl-containing acrylate monomer C has a structure as shown in formula (4-1). The reaction temperature is 70°C, and azobisisobutyronitrile (AIBN) is added at the same time to obtain a resin (M-1) with a thermally cross-linked structure having a molecular weight of 7000.
[0056] Based on the above preparation principle, resins (M-2), (M-3), (M-4), (M-5) and (M-6) having thermal cross-linked structures were prepared, wherein the selection and molar ratio of hydroxyl-containing acrylate monomer A, epoxy acrylate monomer B and carboxyl-containing acrylate monomer C, as well as the molecular weights of the different resins finally prepared are shown in Table 1 below.
[0057] Table 1 Raw material selection, molar ratio and molecular weight of resin (M-1) to resin (M-6)
[0058]
[0059] Comparative Example 1
[0060] This comparative example provides a method for preparing a resin, wherein a hydroxyl-containing acrylate monomer A and a carboxyl-containing acrylate monomer C are mixed in a molar ratio of 20:25, and then added dropwise to a butyl acetate solvent for copolymerization; wherein the hydroxyl-containing acrylate monomer A has a structure as shown in formula (2-5), and the carboxyl-containing acrylate monomer C has a structure as shown in formula (4-2), the reaction temperature is 70°C, and azobisisobutyronitrile (AIBN) is added at the same time to obtain a resin (D-1) having a molecular weight of 7500.
[0061] Comparative Example 2
[0062] This comparative example provides another method for preparing a resin, wherein a hydroxyl-containing acrylate monomer A and an epoxy acrylate monomer B are mixed in a molar ratio of 20:40, and then added dropwise to a butyl acetate solvent for copolymerization; wherein the hydroxyl-containing acrylate monomer A has a structure as shown in formula (2-5), and the epoxy acrylate monomer B has a structure as shown in formula (3-5), the reaction temperature is 70°C, and azobisisobutyronitrile (AIBN) is added at the same time to obtain a resin (D-2) having a molecular weight of 8000.
[0063] Example 1
[0064] The present embodiment provides an optical adhesive composition (I) with thermal reflux effect, which includes the following raw materials in parts by weight: 10 parts of a resin (M-1) with a thermal cross-linking structure, 3 parts of precursor liquid particles, 2 parts of a photoinitiator, 0.1 parts of a surfactant, and 50 parts of a solvent.
[0065] The precursor liquid particles are ZrO2 with an average particle size of 6 nm and a refractive index of 1.85; and the mass ratio of the precursor liquid particles to the resin (M-1) having a thermal cross-linking structure is 3:10;
[0066] The photoinitiator used was OXE-01;
[0067] The surfactant used was BYK-310 manufactured by BYK;
[0068] The solvent is propylene glycol methyl ether acetate.
[0069] The optical adhesive composition (I) with thermal reflow effect prepared in this embodiment is subjected to spin coating, pre-baking, exposure, development, and then heated reflow to form a microlens; wherein the heating temperature is 90°C.
[0070] Example 2
[0071] The present embodiment provides an optical adhesive composition (II) with thermal reflux effect, which includes the following raw materials in parts by weight: 10 parts of a resin (M-2) with a thermal cross-linking structure, 5 parts of precursor liquid particles, 5 parts of a photoinitiator, 0.1 parts of a surfactant, and 50 parts of a solvent.
[0072] The precursor liquid particles are ZnO with an average particle size of 12 nm and a refractive index of 1.85; and the mass ratio of the precursor liquid particles to the resin (M-2) having a thermal cross-linking structure is 5:10;
[0073] The photoinitiator used was OXE-01;
[0074] The surfactant used was BYK-310 manufactured by BYK;
[0075] The solvent is propylene glycol methyl ether acetate.
[0076] The optical adhesive composition (II) with thermal reflux effect prepared in this embodiment is subjected to spin coating, pre-baking, exposure, development, and then heated reflux to form a microlens; wherein the heating temperature is 130°C.
[0077] Example 3
[0078] The present embodiment provides an optical adhesive composition (three) with thermal reflux effect, which includes the following raw materials in parts by weight: 15 parts of a resin (M-3) with a thermal cross-linking structure, 5 parts of precursor liquid particles, 5 parts of a photoinitiator, 0.2 parts of a surfactant, and 50 parts of a solvent.
[0079] The precursor liquid particles are TiO2 with an average particle size of 18 nm and a refractive index of 1.9; and the mass ratio of the precursor liquid particles to the resin (M-3) having a thermal cross-linking structure is 5:15;
[0080] The photoinitiator used was OXE-01;
[0081] The surfactant used was BYK-320 manufactured by BYK;
[0082] The solvent is propylene glycol methyl ether acetate.
[0083] The optical adhesive composition (III) with thermal reflux effect prepared in this embodiment is subjected to spin coating, pre-baking, exposure, development, and then heated reflux to form a microlens; wherein the heating temperature is 140°C.
[0084] Example 4
[0085] The present embodiment provides an optical adhesive composition (four) with thermal reflux effect, which includes the following raw materials in parts by weight: 15 parts of a resin (M-4) with a thermal cross-linking structure, 5 parts of precursor liquid particles, 4 parts of a photoinitiator, 0.3 parts of a surfactant, and 50 parts of a solvent.
[0086] The precursor liquid particles are TiO2 with an average particle size of 18 nm and a refractive index of 1.9; and the mass ratio of the precursor liquid particles to the resin (M-4) having a thermal cross-linking structure is 5:15;
[0087] The photoinitiator used was OXE-02;
[0088] The surfactant used was BYK-320 manufactured by BYK;
[0089] The solvent is propylene glycol methyl ether acetate.
[0090] The optical adhesive composition (IV) with thermal reflow effect prepared in this embodiment is subjected to spin coating, pre-baking, exposure, development, and then heated reflow to form a microlens; wherein the heating temperature is 140°C.
[0091] Example 5
[0092] The present embodiment provides an optical adhesive composition (V) with thermal reflux effect, which includes the following raw materials in parts by weight: 20 parts of a resin (M-5) with a thermal cross-linking structure, 8 parts of precursor liquid particles, 4 parts of a photoinitiator, 0.4 parts of a surfactant, and 50 parts of a solvent.
[0093] The precursor liquid particles are a mixture of SnO2 and TiO2 with an average particle size of 1:1, an average particle size of 20 nm, and a refractive index of 2.0; and the mass ratio of the precursor liquid particles to the resin (M-5) with a thermal cross-linking structure is 2:5;
[0094] The photoinitiator used was OXE-02;
[0095] The surfactant used was BYK-320 manufactured by BYK;
[0096] The solvent is 3-methoxybutyl acetate.
[0097] The optical adhesive composition (V) with thermal reflow effect prepared in this embodiment is subjected to spin coating, pre-baking, exposure, development, and then heated reflow to form a microlens; wherein the heating temperature is 150°C.
[0098] Example 6
[0099] The present embodiment provides an optical adhesive composition (six) with thermal reflux effect, which includes the following raw materials in parts by weight: 20 parts of a resin (M-6) with a thermal cross-linking structure, 10 parts of precursor liquid particles, 3 parts of a photoinitiator, 0.5 parts of a surfactant, and 50 parts of a solvent.
[0100] The precursor liquid particles are selected as a mixture of ZrO2 and TiO2, and the mass ratio of the two is 1:1, the average particle size is 20nm, and the refractive index is 2.0; and the mass ratio of the precursor liquid particles to the resin (M-6) with a thermal cross-linking structure is 5:4;
[0101] The photoinitiator used was OXE-02;
[0102] The surfactant used was BYK-370 manufactured by BYK;
[0103] The solvent is 3-methoxybutyl acetate.
[0104] The optical adhesive composition (VI) with thermal reflow effect prepared in this embodiment is subjected to spin coating, pre-baking, exposure, development, and then heated reflow to form a microlens; wherein the heating temperature is 150°C.
[0105] Comparative Example 3
[0106] Based on Example 1, the difference from Example 1 is that the optical adhesive composition (seven) provided in this comparative example adopts the resin (D-1) prepared in Comparative Example 1; the optical adhesive composition (seven) is spin-coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 130°C.
[0107] Comparative Example 4
[0108] Based on Example 1, the difference from Example 1 is that the optical adhesive composition (eight) provided in this comparative example adopts the resin (D-2) prepared in Comparative Example 2; the optical adhesive composition (eight) is spin-coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 130°C.
[0109] Comparative Example 5
[0110] Based on Example 1, the difference from Example 1 is that the optical adhesive composition (ninth) provided in this comparative example adopts bisphenol A epoxy resin as its resin; the optical adhesive composition (ninth) is spin coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 130°C.
[0111] Comparative Example 6
[0112] Based on Example 3, the difference from Example 3 is that: the optical adhesive composition (ten) provided in this comparative example has a precursor liquid particle weight portion of 1 part; the optical adhesive composition (ten) is spin coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 140°C.
[0113] Comparative Example 7
[0114] Based on Example 3, the difference from Example 3 is that: the optical adhesive composition (XI) provided in this comparative example has 15 parts by weight of precursor liquid particles; the optical adhesive composition (XI) is spin coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 140°C.
[0115] Comparative Example 8
[0116] Based on Example 1, the difference from Example 1 is that the optical adhesive composition (XII) provided in this comparative example is spin-coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 80°C, which is not within the aforementioned temperature range of 90 to 150°C.
[0117] Comparative Example 9
[0118] Based on Example 2, the difference from Example 2 is that the optical adhesive composition (thirteen) provided in this comparative example is spin-coated, pre-baked, exposed, developed, and then heated; wherein the heating temperature is 200°C, which is not within the aforementioned temperature range of 90 to 150°C.
[0119] Comparative Example 10
[0120] On the basis of Example 2, the difference from Example 2 is that: the optical adhesive composition (fourteen) provided in this comparative example uses resin (D-3); compared with D-2 prepared in Comparative Example 2, D-3 is different in that the hydroxyl-containing acrylate monomer A is selected from the structure shown in the following formula (5) and is spin-coated, pre-baked, exposed, developed, and then heated;
[0121]
[0122] Here, the applicant needs to explain that the process of preparing the microlens based on the above optical adhesive composition in the present invention is as follows:
[0123] Step 1: First, the optical adhesive composition is coated on a silicon nitride substrate. The optical adhesive composition can be coated by a spin coater, a coater, a roller coating method, a slit coating method or other coating methods, and then pre-baked at 85° C. for 1.5 min to form a 3 μm coating film;
[0124] Step 2, then, the coating film is exposed to obtain a film having a target pattern, and irradiated with 365nm ultraviolet rays using a mask having a line / space pattern of 1 to 50 μm, so that the film cured by ultraviolet irradiation is brought into contact with a developer to dissolve the unexposed area for development, and after development, the pattern is washed with water of tetramethylammonium hydroxide and blown dry with nitrogen;
[0125] Step 3: Finally, the developed silicon nitride substrate is heated at 90 to 150° C. for 3 to 20 minutes to melt and flow the adhesive film, thereby thermally reflowing to form a photocured pattern, which can be directly used as a microlens.
[0126] Performance Testing
[0127] (1) Adhesion: Use a grid cutting disc and a utility knife to cut the coating into grids; stick 3M transparent tape on the grids and apply force to make the tape firmly stick to the coating surface and the grid areas. Visually observe the peeling phenomenon and degree of the coating on the substrate to determine its ASTM grade. The ASTM grades are as follows: 5B - the cut edge is smooth, and there is no peeling on the grid edge; 4B - the peeling area in the grid area is ≤5%; 3B - the peeling area in the grid area is greater than 5% to 15%; 2B - the peeling area in the grid area is greater than 15% to 35%; 1B - the peeling area in the grid area is greater than 35% to 65%; 0B - the peeling area in the grid area is greater than 65%.
[0128] (2) Refractive index:
[0129] A 5cm×5cm×1.5μm (width×length×thickness) adhesive film is formed on the upper surface of a silicon nitride substrate. The sample is prepared according to the method for forming a solidified pattern, except that no mask is used. An ellipsometer is used for test fitting, and the wavelength corresponding to the refractive index value is selected as 550nm.
[0130] (3) Light transmittance:
[0131] The samples were prepared according to the method of forming the cured pattern except that no mask was used, and the transmittance of the cured single film (whole surface unpatterned) in the visible light range of 380nm to 800nm was measured by a UV-visible spectrophotometer (U-3900 Hitachi).
[0132] (4) Reflow property: Samples were prepared according to the method for forming a solidified pattern, and different heating temperatures were used in step 3. Samples that could reflow and had a good microlens shape were marked as ◎, samples that could reflow and had a poor microlens shape were marked as ○, and samples that could not reflow were marked as ×.
[0133] (5) Yellowing index YI: Xenon lamp aging test test conditions: 0.55W / m 2 @340nm, 40℃, 20%-30%RH, 300-800nm illumination for 20h + 4h room temperature storage (no light), 10 cycles for a total of 240h. Measured using UV-Vis spectrophotometer according to ASTME313 standard.
[0134] In order to further verify the effectiveness of the technical solution provided by the present invention, the performance of the photocurable patterns formed by the above-mentioned Examples 1 to 6 and Comparative Examples 3 to 9 was tested, and the results are shown in Table 1 below:
[0135] Table 1 Test results of photocured patterns formed in Examples 1 to 6 and Comparative Examples 3 to 9
[0136] Test items Adhesion Refractive index / % Light transmittance / % Reflow Yellowing Index Example 1 5B 1.5882 98.8 ◎ 0.6 Example 2 5B 1.6054 98.5 ◎ 0.5 Example 3 5B 1.5921 98.3 ◎ 0.6 Example 4 5B 1.5973 98.2 ◎ 0.7 Example 5 5B 1.6063 98.0 ◎ 0.6 Example 6 4B 1.6132 98.0 ◎ 0.8 Comparative Example 3 4B 1.5895 98.7 ◎ 1.2 Comparative Example 4 3B 1.5889 98.7 × 1.5 Comparative Example 5 2B 1.5935 97.9 ○ 1.6 Comparative Example 6 4B 1.5512 98.8 ◎ 1.7 Comparative Example 7 2B 1.6315 96.7 × 1.9 Comparative Example 8 3B 1.6049 96.5 × 2.1 Comparative Example 9 3B 1.6054 96.2 × 2.5 Comparative Example 10 2B 1.6051 97.1 ○ 8.1
[0137] As shown in Table 1 above, the yellowing index of the photocured patterns formed in Examples 1 to 6 is less than 0.8. The photocured patterns corresponding to Examples 1 to 5 have a higher refractive index and transmittance, and the adhesion can reach 5B. At the same time, reflow can occur, and the formed lens has a good shape with high precision and integrity. Example 6 uses the acrylic monomer A resin (M-6) without adding hydroxyl groups, and the adhesion is 4B, and other properties are excellent.
[0138] In contrast, the adhesion in Comparative Examples 3 to 9 is 2 to 4B, and the yellowing index is greater than 1. Specifically:
[0139] In comparative example 3, the resin (D-1) prepared without epoxy acrylic monomer B was used, and in comparative example 4, the resin (D-2) prepared without carboxyl acrylate monomer C was used, which affected the adhesion and reflow properties. Comparative example 5 used bisphenol A epoxy resin, which had poor adhesion and poor reflow shape.
[0140] In Comparative Examples 6-7, the amount of precursor liquid particles added is too little or too much, and is not within the required range of 3-10 parts, which affects the refractive index and transmittance, and the overall performance of the corresponding photocurable patterns is poor.
[0141] The heating temperature of Comparative Example 8 is relatively low and does not reach the hot reflux temperature, so reflux does not occur; the heating temperature of Comparative Example 9 is too high, and the optical adhesive composition forms a network structure and is directly shaped; in Comparative Example 10, a resin composition containing aromatic rings is used, which produces more serious yellowing phenomenon, with a yellowing index greater than 8, and the adhesion is also affected.
[0142] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0143] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A resin having a thermal cross-linking structure, characterized in that: Its general structure is as follows: In formula (1), R1 is a methyl group or H, R2 and R4 represent a hydrocarbon group or an alkoxy group, R3 is an epoxy group, and R5 and R6 are each independently a hydrogen atom, a halogen atom, a C1-C4 alkyl group or a C1-C4 fluorinated alkyl group; * indicates the bond with the main chain; x=0~30mol%, y=40~60mol%, z=20~40mol%.
2. The resin having a thermal cross-linking structure according to claim 1, characterized in that: The molecular weight of the resin is 7000-10000.
3. The resin having a thermal cross-linking structure according to claim 1, characterized in that: The epoxy group includes any one of the following formulas (1-1) to (1-6): Wherein, * is a connection site; R7 and R8 are any one of H, C1 to C6 alkyl, C1 to C6 fluoroalkyl, and alkenyl.
4. The method for preparing a resin having a thermal cross-linking structure according to any one of claims 1 to 3, characterized in that: A hydroxyl-containing acrylate monomer A, an epoxy acrylate monomer B, and a carboxyl-containing acrylate monomer C are mixed, and then added dropwise to a reaction solvent for copolymerization, and a free radical initiator is added for synthesis to obtain a resin with a thermal cross-linking structure.
5. The method for preparing a resin having a thermal cross-linking structure according to claim 4, characterized in that: The general structural formula of the hydroxyl-containing acrylate monomer A is as follows: (2), the general structural formula of the epoxy acrylate monomer B is as follows: (3), and the general structural formula of the carboxyl-containing acrylate monomer C is as follows: Among them, R1 is methyl or H, R2 and R4 represent hydrocarbon groups or alkoxy groups, R3 is an epoxy group, and R5 and R6 are independently hydrogen atoms, halogen atoms, C1-C4 alkyl groups or C1-C4 fluorinated alkyl groups.
6. An optical adhesive composition having a thermal reflow effect, characterized in that: The invention comprises at least the following raw materials by weight: 10 to 20 parts of a resin having a thermal cross-linking structure as claimed in any one of claims 1 to 3, 3 to 10 parts of precursor liquid particles, 1 to 5 parts of a photoinitiator, 0.01 to 0.5 parts of a surfactant, and 40 to 80 parts of a solvent.
7. The optical adhesive composition having a thermal reflow effect according to claim 6, characterized in that: The precursor liquid particles are selected from one or two of ZrO2, TiO2, In2O3, Al2O3, ZnO or SnO2.
8. The optical adhesive composition having a thermal reflow effect according to claim 6, characterized in that: The photoinitiator includes an oxime ester photoinitiator, and the oxime ester photoinitiator includes any one or at least two of OXE-01, OXE-02, OXE-E12 or OXPI-405.
9. A microlens, characterized in that: The method is formed by thermal reflowing the optical adhesive composition having the thermal reflow effect as described in any one of claims 6 to 8.
10. A method for preparing a microlens as claimed in claim 9, characterized in that: The optical adhesive composition with heat reflow effect as claimed in any one of claims 6 to 8 is coated on a substrate and pre-baked to obtain a coating film; then the coating film is exposed to light to obtain an adhesive film with a target pattern; then the adhesive film is developed, rinsed, exposed again, and finally heated and reflowed to form a microlens.
Citation Information
Patent Citations
Radiation-sensitive resin composition and process for forming microlens
CN111352301A
Photosensitive resin composition for microlenses
CN103229101A
Resin having thermal crosslinked structure and method for preparing same, photosensitive resin composition, microlens and method
CN115960303A
Microlens forming composition, method for manufacturing microlens using composition, cured film, solid state image sensor and imaging device
JP2022156546A
Photosensitive resin composition and microlens formed with use thereof
TW200923573A